Determining the Effect of Varying Magmatic Volatile Content on Lunar Magma Ascent Dynamics. Issue 11 (29th October 2021) - Lo, M.; La Spina, G.; Joy, K. H.; Polacci, M.; Burton, M.
Abstract: The Moon is not volcanically active at present, therefore, we rely on data from lunar samples, remote sensing, and numerical modeling to understand past lunar volcanism. The role of different volatile species in propelling lunar magma ascent and eruption remains unclear. We adapt a terrestrial magma ascent model for lunar magma ascent, considering different compositions of picritic magmas and various abundances of H2, H2 O, and CO (measured and estimated) for these magmas. We also conduct a sensitivity analysis to investigate the relationship between selected input parameters (pre‐eruptive pressure, temperature, conduit radius, and volatile content) and given outputs (exit gas volume fraction, velocity, pressure, and mass eruption rate). We find that, for the model simulations containing H2 O and CO, CO was more significant than H2 O in driving lunar magma ascent, for the range of volatile contents considered here. For the simulations containing H2 and CO, H2 had a similar or slightly greater control than CO on magma ascent dynamics. Our results showed that initial H2 and CO content has a strong control on exit velocity and pressure, two factors that strongly influence the formation of an eruption plume, pyroclast ejection, and overall deposit morphology. Our results highlight the importance of (a) quantifying and determining the origin of CO, and (b) understanding the abundance of different H‐species present within the lunar mantle. Quantifying the role of volatiles in driving lunar volcanism provides an important link between the interior volatile content of the Moon and the formation of volcanic deposits on the lunar surface. Plain Language Summary: Unlike the Earth, the Moon does not have any active volcanoes, and has not had any active volcanoes for at least the last 100 million to 1 billion years. Therefore, we rely on studying samples collected by astronauts and robotic landers, satellite data, and computer models to understand what volcanic activity on the Moon was like. Volcanic eruptions are mostly driven by gas: as magma rises in the Moon's crust, gases will separate out, allowing magma to rise more quickly. As a result of this, we can use volcanic eruptions to understand how much gas exists within the Moon, which is important for understanding how the Moon formed. We used a computer model to simulate magma ascent on the Moon in order to understand what gases were more significant in driving magma ascent. We found that molecular hydrogen and carbon monoxide had a bigger effect on magma ascent than water, so would have a greater effect on the style of volcanic eruptions on the Moon. The source of carbon monoxide and the relative amounts of molecular hydrogen and water in the Moon's mantle are currently unknown and our results highlight the importance of understanding this information for understanding lunar volcanic activity. Key Points: We use a magma ascent model and sensitivity analysis to understand the relative significance of different volatiles on lunar magma ascent For the range of initial volatile abundances considered, CO and H2 were more significant than H2 O in driving lunar magma ascent Results highlight the importance of quantifying and determining the origin of CO, and understanding H‐speciation within the lunar mantle